2020
DOI: 10.1111/rda.13826
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of candidate genotype of leptin gene associated with fertility and production traits in Hardhenu (Bos taurus × Bos indicus) cattle

Abstract: The present study was conducted on Hardhenu cattle to screen genomic region of leptin gene with an objective to find the association of genotypes with fertility and production traits. The association analysis with traits under study was analysed by least squares analysis of variance by taking SNPs genotype as fixed effects in the statistical model. The genotypic frequencies with respect to targeted loci g.92450765 G > A indicated that AG (0.54) genotype was highest in Hardhenu cattle. Chi-squared tests showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Matumoto et al ( 2022) reported that SNP c.239C>T (p.A80V) in leptin gene had significant effects on the traits related with quality grade; beef marbling standard (p: 0.0132), meat brightness (p: 0.0383), and meat firmness (p: 0.0115). Yadav et al (2020) reported that SNP has contribution to estrus and physical condition scores. The leptin gene has been reported to affect parenting each year (D'occhio et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Matumoto et al ( 2022) reported that SNP c.239C>T (p.A80V) in leptin gene had significant effects on the traits related with quality grade; beef marbling standard (p: 0.0132), meat brightness (p: 0.0383), and meat firmness (p: 0.0115). Yadav et al (2020) reported that SNP has contribution to estrus and physical condition scores. The leptin gene has been reported to affect parenting each year (D'occhio et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…They found two alleles and three genotypes in all four cattle breeds. Yadav et al, (2020) analyzed the genomic region of the leptin gene and found an association of production traits with all three genotypic patterns-AA, AG and GG in Hardhenu cattle. 3).…”
Section: Gene and Genotypic Frequency Of Exon-3 Of Lep Genementioning
confidence: 99%
“…The low productivity of indigenous animals and production and reproduction‐related diseases, such as mastitis, metritis and retention of placenta and dystocia in high‐yielding cattle are major concerns for the dairy industry. The susceptibility/resistance to mastitis and reproductive disorders is a threshold trait which is having low heritability (Falconer, 1965; Magotra et al, 2020; Yadav et al, 2020). Mastitis and reproductive disorders are among the most prevalent and economically detrimental health issues in dairy (García‐Sánchez et al, 2018; Kamaldeep et al, 2021; Krishnamoorthy et al, 2021; Rupp & Boichard, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…trait which is having low heritability (Falconer, 1965;Magotra et al, 2020;Yadav et al, 2020). Mastitis and reproductive disorders are among the most prevalent and economically detrimental health issues in dairy (García-Sánchez et al, 2018;Kamaldeep et al, 2021;Krishnamoorthy et al, 2021;Rupp & Boichard, 1999).…”
mentioning
confidence: 99%